International Conference «Tumor Hypoxia and Malignant Progression». October 1–4, 2008, House of Scientists of NASU, Kiev, Ukraine - Zhang, G.; Huang, Z.; Shi, R.; Lin, Y.; Hao, B. (Experimental Oncology, 2008)
Tumor hypoxia: pathophysiological and molecular mechanisms; Hypoxia and HIF-1: role in tumor progression; Evaluation of tumor oxygenation; Hypoxia-modulated tumor stroma; Hypoxia and glycolysis in tumor: mechanisms of interrelationship;Hypoxia and tumor-host interface; Hypoxia-induced metastasis; Tumor hypoxia: therapeutic resistance and hypoxia-related therapies; Hypoxia and prognosis of clinical outcome